Improving Students’ Speaking Skill Using Role-Play Method: Study Case In Lubna Children, Central Lombok. - Moh. Hamdi Hardi; Baiq Ulfiya Hafizah; Kamilia Kamilia; Jatmika Aripadana; Selamet Riadi Jaelani (LPPM Politeknik Pratama, 2023)
This article presents a study conducted at Lubna Children, Central Lombok, Indonesia. This article aims to discuss the use of role-play method in improving students' speaking skills. This study uses a qualitative research design with a case study approach. Data was collected through class observation and students' speaking tests before and after the application of the role-play method. This research has provided several significant findings related to the application of the role-play method in improving students' speaking skills at Lubna Children, Central Lombok. Role-play method in this study has proven its effectiveness in improving students' speaking skills at Lubna Children, Central Lombok. The role-play method can be considered an interesting and effective alternative for improving students' speaking skills in an educational setting.